Synergistic potential of bone marrow mesenchymal stem cells and miR181-a combinational therapy against multiple sclerosis - Xin Xiu; Sijia Chen; Yumei Liu; Bo Sun; Hulun Li; Sifan Zhang; Xixi Yang; Yu Wei; Xichen Peng; Yan Wang; Yanping Wang; Junfeng Wu; et al. (Stem Cell Research & Therapy)
Abstract Background Multiple sclerosis (MS) is a progressive autoimmune disease characterized by massive inflammatory infiltration, demyelination, and subsequent axonal injury and neuronal damage in the central nervous system (CNS). The etiology of MS remains unclear and there is not yet a definitive therapeutic schedule for the disease. Bone marrow mesenchymal stem cells (BMSCs), exhibiting neuroimmune-modulatory functions to alleviate various autoimmune diseases, show great potential in the treatment of MS. However, the instability of BMSCs-mediated immunosuppression in vivo has limited their application. MiR181-a, a positive regulator of immune balance, which has a preference for T cells and B cells differentiation, but degrade rapidly upon entering systemic circulation due to their unstable molecular structure. Methods We propose a synergistic therapy approach that combines the penetrative targeting capability of BMSCs with the immuno-modulatory effects of miR181-a by overexpressing miR181-a to BMSCs through lentivirus packaging system. With this strategy, on the basis of the establishment of the experimental autoimmune encephalomyelitis (EAE) model, miR181-a overexpressing BMSCs (miR181a-BMSCs) would have a stronger immuno-modulatory treatment benefit, in terms of attenuating MS development. Results Indicate that this method prolongs the modulatory effects of BMSCs and resulted in significantly enhancements of the proliferation of regulatory B cells (Bregs), regulatory T cells (Tregs) and the inhibition of Th17 cells compared to the traditional BMSCs group. Moreover, 10-fold miRNA’s concentration in the exosome of miR181a-BMSCs, leading to an increased duration of miRNAs to exert their biological effects. By immunotherapy and synergistic treatment, the effectiveness of the treatment is significantly enhanced, showing consistent results in different groups of the animal model. Conclusions This strategy takes advantage of BMSCs and miRNA and thus presents an effective synergistic strategy for the treatment of autoimmune diseases.